Analysis of the Themes of Corporate Social Responsibility (CSR) 2013-2020 - Nurul Andani; Bambang Shergi Laksmono (Budapest International Research and Critics University, 2022)
This study aims to look at the concepts used in student thesis research based on their development from time to time and also in this study to see the implementation of CSR carried out by companies based on student theses in the 2013-2020 period. The data used in this study is the thesis data of postgraduate students in Social Welfare Sciences from 2013 to 2020 with the theme of CSR. The results of the research in the thesis research of social welfare science students at the University of Indonesia in the 2013-2020 range that the most widely used CSR concepts are the concepts in the 2001-2010 timeframe. In the implementation of CSR, the dominance of the application carried out by the company based on the type of application is to use the cause promotion type, organizational governance), issues of human rights (human rights) and also social development (social development) dominate compared to other categories.